Analysis Of The Impact Of The Covid-19 Pandemic On The Construction Industry Sector - Liliana Hannes; Julistyana Tistogondo (Neutron, 2022)
Accelerating infrastructure development in Indonesia is a good thing, but this is not without problems. The COVID-19 pandemic is a problem that has a large and global impact, not least in Indonesia, especially in the construction industry sector. The construction project of the Soedono Madiun Hospital is one of the construction projects that have experienced the direct impact of the COVID-19 pandemic. Therefore, the purpose of this study is to review and analyze the impact of the covid-19 pandemic on construction projects in the case study of the construction project of the Soedono Madiun Hospital, and to find out the biggest impact of the covid-19 pandemic which has the most influence on construction projects in the case study of the construction project of the Soedono Hospital. Madison. The research method used to determine the biggest impact of the covid-19 pandemic on the cost and time aspects is the multiple linear regression analysis method with the help of Microsoft Excel. The other data analysis methods used in this study were the validity and reliability tests used in testing the questionnaire. The results of data analysis conducted in this study indicate that there are seven independent variables affect the dependent variable, namely the suitability of planning and project realization with the equation y= 94.186-0.376x1-0.108x2-1.014x3+0.873x4 for the time aspect, and the equation y=87,009 -0.0006x5-0.001x6-0.0002x7 for the cost aspect. With this equation, it can be seen that the independent variable that has the most influence on the dependent variable on the time aspect is the independent variable X3, namely the change in the time schedule due to delays in the arrival of construction materials by 1.014, while in the cost aspect is the independent variable X6, namely changes in costs due to instability. the price of construction materials is 0.001. So, it is hoped that there will be a project management handling that focuses on the most influential variable, namely construction materials.